2022
DOI: 10.3390/molecules27061870
|View full text |Cite
|
Sign up to set email alerts
|

Using Taguchi Method to Determine the Optimum Conditions for Synthesizing Parapyruvate

Abstract: The synthesis of parapyruvate is important for the analysis of the content in the pyruvate supplements and the study of aging-related neurodegenerative diseases. However, the pure parapyruvate crystal is not, as yet, commercially available. In this study, we applied the Taguchi’s L9 orthogonal array to investigate the optimal conditions for the preparation of the pure parapyruvate by the alkaline treatment of the pyruvic acid and then followed it with the solvent crystallization steps. We were also interested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…As mentioned above, the formation of citramalate might be the consequence of either a condensation reaction between the produced acetate and pyruvate or of a decarboxylation of the produced parapyruvate. Parapyruvate is a well-known and widely reported homo-aldol condensation product of pyruvate [84][85][86] , which is more favored under alkaline conditions 87 . To investigate the role of pH for pyruvate conversion to citramalate, two more parallel reactions were performed at pH 7 and 9 with the addition of KOH, and the outcomes are presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, the formation of citramalate might be the consequence of either a condensation reaction between the produced acetate and pyruvate or of a decarboxylation of the produced parapyruvate. Parapyruvate is a well-known and widely reported homo-aldol condensation product of pyruvate [84][85][86] , which is more favored under alkaline conditions 87 . To investigate the role of pH for pyruvate conversion to citramalate, two more parallel reactions were performed at pH 7 and 9 with the addition of KOH, and the outcomes are presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have shown that parapyruvate is a reversibly competitive inhibitor of the KGDHC activity and can induce senescence in Hs68 cells by inhibiting the cellular KGDHC activity. 2,5 In this study, we administered parapyruvate to the C57BL/6JNarl mice at dosages ranging from 5 to 500 mg/kg/ day and observed a dose-dependent impairment of the learning and memory ability. Furthermore, we observed that parapyruvate both decreased the KGDHC activity and increased the oxidative stress in the brain in a dose-dependent manner, as evidenced by the decreased levels of GSH and the SOD activity and the increased levels of MDA and nitrite in the brain.…”
Section: Discussionmentioning
confidence: 94%
“…Parapyruvate is formed by the aldol addition reaction of two molecules of pyruvate and is commonly found in commercial dietary supplements of calcium pyruvate (DSCP). Parapyruvate is a reversibly competitive inhibitor of the α-ketoglutarate dehydrogenase complex (KGDHC) with a structure similar to α-ketoglutarate (α-KG), which is the substrate of KGDHC . Parapyruvate can also be used as an inhibitor of the tricarboxylic acid cycle (TCA) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Taguchi method has been widely used in various industries, including manufacturing, engineering, and product development, to improve quality, reduce variability, and enhance overall performance. It provides a systematic and efficient approach to experimental design and optimization, making it a valuable tool for quality improvement initiatives [18][19][20][21][22]. For example, the Taguchi experimental design was applied to optimize the vacuum printing encapsulation process, where a combination of process parameters was considered, including the squeegee moving speed, printing delay time, and the number of squeegee printings [18].…”
Section: Introductionmentioning
confidence: 99%